2010
DOI: 10.1007/s00606-010-0327-9
|View full text |Cite
|
Sign up to set email alerts
|

A phylogenetic analysis of the genus Paspalum (Poaceae) based on cpDNA and morphology

Abstract: With about 350 species, Paspalum is one of the richest genera within the Poaceae. Its species inhabit ecologically diverse areas along the Americas and they are largely responsible for the biodiversity of grassland ecosystems in South America. Despite its size and relevance, no phylogeny of the genus as a whole is currently available and infrageneric relationships remain uncertain. Many Paspalum species consist of sexual-diploid and apomicticpolyploid cytotypes, and several have arisen through hybridization. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
68
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 55 publications
12
68
0
10
Order By: Relevance
“…Previous molecular phylogenetic studies [99] have suggested a greater genetic distance between the third main group compared to the Plicatula and Notata groups, which explains the lower frequency of microsatellite polymorphisms observed for species from the third group. However, there was a clear distinction between the species of this group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous molecular phylogenetic studies [99] have suggested a greater genetic distance between the third main group compared to the Plicatula and Notata groups, which explains the lower frequency of microsatellite polymorphisms observed for species from the third group. However, there was a clear distinction between the species of this group.…”
Section: Discussionmentioning
confidence: 99%
“…notatum and P . subciliatum [99-101] (these species form a monophyletic clade). Moreover, whether P .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morfológicamente las plantas de Paspalum se caracterizan por presentar espiguillas biflosculares plano convexas, siendo ésta probablemente la única sinapomorfia del género (Rua et al, 2010). Además, las espiguillas generalmente carecen de la primera gluma y la lema fértil presenta los márgenes enrollados (Chase, 1929;Hitchcock, 1971).…”
Section: Introductionunclassified
“…Han sido numerosos los trabajos encaminados a esclarecer la clasificación infragenérica de Paspalum (Döll, 1877;Nash, 1912;Chase, 1929;Pilger, 1929;Zuloaga, 1974;Clayton y Renvoize, 1986;Cialdella et al, 1995;Denham et al, 2002;Morrone et al, 1995Morrone et al, , 1996Morrone et al, , 2000Morrone et al, , 2004Rodríguez, 1992Rodríguez, , 1998Zuloaga y Morrone, 2003, 2005Zuloaga et al, 2004;Denham, 2005;Denham et al, 2010). Sin embargo, no existe un esquema natural de clasificación dentro del mismo (Rua et al, 2010), ya que dichas propuestas se basan en macrocaracteres morfológicos que se presentan en grupos de especies aparentemente poco relacionadas (Zuloaga y Morrone, 2005). En el presente trabajo, acorde con los trabajos de Zuloaga et al (2004), Zuloaga y Morrone (2005), Denham (2005) y Denham et al (2010), basados en los estudios previos de Nash (1912) y Chase (1929), se reconocen cuatro subgéneros: subg.…”
Section: Introductionunclassified